ANALISIS DATA SEISMOGRAM YANG DIREKAM DI STASIUN XMI - Arizza Darwis J., ; Supardiyono, (Matematika dan Sains, 2009)
The aims of research is to verify the earth crustal model through seismogram analysis of earthquake at the Sunda strain at 19 July 2006 10:57:36.8 UTC and to know the depth of upper layer (km), wave speed P (Vp), wave S (Vs) and medium density (Rho). Seismogram data was take from one station (XMI.AU) around epicenter which has distance of 436.4950 km from earthquake centre. The all data were analyzed using waveform 3 component and invertion method. The results of research showed that correlation and varian of reduction between observation seismogram and syntetic of earth crustal model producing as much as 91% and 82,67 %, respectively. The depth of first, second, thirth, fourth, and five layers were 1 km, 1 km, 3 km, 11 km and 17 km, respectively. The value of correlation and reduction varian resulted were better than the other earth crustal model. It showed that the earth crustal model used at around XMI station has high validity.